Healthcare Cost Savings Estimator Tool for Chronic Disease Self-Management Program: A New Tool for Program Administrators and Decision Makers - Ahn, SangNam; Smith, Matthew Lee; Altpeter, Mary; Post, Lindsey; Ory, Marcia G. (Frontiers in Public Health, 2015)
*